2009
DOI: 10.1007/s10661-009-1064-9
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of heavy metals in fresh water fish species of the River Ravi, Pakistan compared to farmed fish varieties

Abstract: The untreated industrial and sewage wastes arising from industries and metropolitan activities make their passage to the River Ravi, Pakistan, where Balloki Headworks is one of the major sites of effluent concentration. This study was designed to evaluate the concentration of various toxic elements in fishes of that area compared to a nearby fish farm. The concentrations of heavy metals, such as As, Cd, Cu, Pb, Hg, and Zn, and electrolytes Ca, K, and Na were determined in different edible and non-edible fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
0
14
1
Order By: Relevance
“…Agarwal [13] reported accumulation of Hg and Pb contents in muscles of wild fish species from the River Gomti, India. Rauf [14], Javed [15], Tariq et al [16], Nawaz et al [17], and Tariq [18] reported effects of trace metals on commercial fish species from various parts of Pakistan. However, no systematic study has been conducted on spatial and temporal variations of heavy metal contents in different edible fish species from Pakistan and in particular to our study area.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal [13] reported accumulation of Hg and Pb contents in muscles of wild fish species from the River Gomti, India. Rauf [14], Javed [15], Tariq et al [16], Nawaz et al [17], and Tariq [18] reported effects of trace metals on commercial fish species from various parts of Pakistan. However, no systematic study has been conducted on spatial and temporal variations of heavy metal contents in different edible fish species from Pakistan and in particular to our study area.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, fish products represent only up to 10% of human diet; nevertheless, they represent the main uptake routes of metals (especially Hg) into the human body (Bienelli and Provini 2004;Chi et al 2007;Deshpande et al 2008;Storelli 2008;Ruelas-Inzunza et al 2010). Human health risk due to the consumption of fish loaded with metals is the subject of many recent studies (HasShön et al 2007b;Castro-Gonzales and MendezArmenta 2008;Türkmen et al 2009); furthermore, it has been shown that in some cases the intake of fish should be regulated (Chi et al 2007;Adhikari et al 2009;Nawaz et al 2009). Castro-Gonzales and Mendez-Armenta (2008) suggested not only that people should eat smaller quantities of fish known to accumulate mercury but also that they should eat a diversity of fish in order to avoid consuming unhealthy quantities of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…However these concentrations are considerable lower than those recently reported in edible freshwater fish species (41 -61.5 µg/g) collected from the Ravi River, Pakistan [31]. It must be pointed out that the toxic properties of As are directly related to its chemical form [32].…”
Section: Resultsmentioning
confidence: 89%